Hpv infections – knowledge among nursing students from Poland and Turkey - Nagórska, Małgorzata; Karabulutlu, Özlem; Wardak, Katarzyna; Binkowska-Bury, Monika (European Journal of Clinical and Experimental Medicine, 2013)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. According to the World Health Organization (WHO), Sexually Transmitted Diseases (STD) are the diseases caused by germs transmitted during sex, starting with easy to treat inflammations, ending up with serious deadly infections. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to compare the knowledge among nursing students in Poland and Turkey about HPV, its etiology and diagnostics. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method. The survey was conducted in an academic year 2009/2010. The questionnaire was completed by nursing students from the University of Rzeszów in Poland and nursing students from Ataturk University, in Erzurum, Turkey. The choice of the research population was purposeful. The studies were conducted among the total number of 224 respondents, 120 in Poland and 124 in Turkey. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Nursing students have high self-rated knowledge about STD (93.0%). Books and journals (63.5%) were mentioned as the most common source of knowledge about sexual health. Among sexually transmitted diseases the respondents mentioned: AIDS (93.0%), gonorrhea (80.8%), HPV (56.5%), HSV (54.9%). Among the respondents 11.9% have never heard of HPV. Every third student does not have any knowledge about vaccinations against HPV (30.4%). Above 40% of respondents are not aware of the recommended frequency of cytological examinations (43,0%) and nearly 60% of them do not know what a colposcopy is. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. Students have high self-rated knowledge about STD. Students from Erzurum, Turkey had better knowledge about HPV diagnostics. Students from both countries showed unsatisfactory knowledge about cervical cancer diagnostics. The level of nursing students’ knowledge as future health educators, both in Poland and Turkey about HPV is insufficient, therefore it is necessary to add supplements about STD to nursing education programs in both countries .